Accuracy of Spleen Measurement by Medical Residents Using Hand‐Carried Ultrasound. (27th October 2015) - Arishenkoff, Shane; Eddy, Christopher; Roberts, J. Mark; Chen, Luke; Chang, Silvia; Nair, Parvathy; Hatala, Rose; Eva, Kevin W.; Meneilly, Graydon S.
Abstract : Objectives: Easily palpable splenomegaly can be identified on physical examination, but it is difficult to detect lesser degrees of splenomegaly. Rapid bedside assessment can be conducted with hand‐carried ultrasound. We performed this study to determine whether medical residents could reliably assess spleen size using hand‐carried ultrasound after a brief educational intervention. Methods: Postgraduate year 1 internal medicine residents were shown a brief (45‐minute) presentation on ultrasound basics, the use of hand‐carried ultrasound, and principles of splenic ultrasound imaging. They practiced on each other, using hand‐carried ultrasound to assess spleen size, for 1 hour in the presence of an instructor. Patients with varying degrees of splenomegaly and hospital staff were recruited at Vancouver General Hospital. A sonographer measured spleen size in each participant using conventional ultrasound. Subsequently, the trained residents scanned the participants using hand‐carried ultrasound, blinded to the sonographer's measurements and the participants' diagnoses. The instructor was not present during scanning. Results: Twelve first‐year residents (8 male and 4 female; mean age ± SEM, 28 ± 1 years; all with limited prior ultrasound training) and 19 patients and staff members (10 male and 9 female; mean age, 60 ± 4 years; body mass index, 24 ± 2 kg/m 2 ) were recruited. The greatest longitudinal measurements were 14.0 ± 0.7 cm with conventional ultrasound administered by the sonographer and 13.2 ± 0.9 cm with hand‐carried ultrasound administered by the residents ( P > .05, not significant). The correlation between conventional and hand‐carried ultrasound was r = 0.81 ( P < .001). Conclusions: Internal medicine residents can reliably assess spleen size at the point of care using hand‐carried ultrasound with minimal training. Our findings, if replicated in other centers and in different clinical scenarios, may change the way that clinicians examine the spleen.